Cloud-edge-device fusion architecture oriented to spectrum cognition and decision in low altitude intelligence network - Chao DONG; Yuqian JING; Yuben QU; Bo ZHOU; Yang HUANG; Ziye JIA; Haipeng DAI; Qihui WU (Tongxin xuebao)
A new architecture for the typical application scenario of low altitude intelligence network spectrum cognition and decision was introduced.Firstly, the challenges of spectrum security management and efficient sharing in low altitude intelligence network were analyzed, and the key scientific problems that need to be solved were summarized.Secondly, to support the spectrum management and sharing of low altitude intelligence network through deep integration of cloud, edge, and device, the cloud-edge-device fusion architecture for low altitude intelligence network spectrum cognition and decision was proposed.Then, the key technologies such as fast and accurate spectrum recognition and agile adaptive decision making based on cloud-edge-device fusion were discussed.Finally, the future research direction of the architecture was introduced.